The Service Delivery Lens: A Study of Citizen’s Charter Implementation from Service Provider’s Perspective - Asad, Md. Asaduzzaman Mondol (The Jahangirnagar Review, 2024)
Citizen Charter is a crucial framework in public organisations, highlighting the importance of transparency, accountability, and responsiveness in providing citizens with high-quality services. This qualitative research study investigates the implementation of the Citizen’s Charter in public organizations within Chandpur and Rangpur District of Bangladesh, from service provider’s perspective. Using structured questionnaires for in-depth interviews, data were collected from 40 key stakeholders, including Chairman/Mayors, members, and service providers, selected through purposive sampling techniques. The findings reveal a notable improvement in the quality of services provided by both municipalities and union parishads following the Citizen’s Charter’s implementation. However, the study also uncovers several challenges in the implementation process, such as a lack of expertise, limited awareness, resource constraints, budget limitations, inadequate monitoring, and issues related to politicization. The research concludes with recommendations to address these challenges and enhance the Citizen’s Charter’s effectiveness, ultimately aiming to encourage more participatory, equitable, and accountable practices among stakeholders and prompt authorities to take necessary steps for improvement.